Impact of Probiotics or Synbiotics Supplementation on Weight Gain and Diarrhea in Children with Severe Acute Malnutrition: A Systematic Review and Meta-Analysis - Sabrina, Hermelien; Tsania, Nadira Muthi; Prasadajudio, Mirari (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Malnutrition remains a critical global health concern, with both short- and long-term consequences. Children suffering from malnutrition frequently exhibit gut dysfunction, which leads to growth retardation, impaired absorption of essential nutrients and vitamins, and immune dysfunction. Diarrhea is one of the most common conditions in children with malnutrition and can further worsen their condition. Probiotics have been proposed as a potential adjunctive therapy in malnutrition due to their role in modulating gut microbiota. This study aims to evaluate the effects of probiotics on weight gain and diarrhea specifically in children with severe acute malnutrition (SAM). Methods: A systematic literature search was conducted across six databases (PubMed, Cochrane Library, ProQuest, EBSCOhost, ScienceDirect, Google Scholar) using relevant keywords. Data were extracted and analyzed using Review Manager for meta-analysis. Result: Four studies, encompassing a total 1662 patient met the inclusion criteria. Probiotics are proven to reduce significantly the duration of diarrhea and improve the recovery (SMD -0.70; 95% CI -0.89 to -0.50; I² = 0%, p < 0.00001). However, they are not diminishing the incidence of diarrhea. Moreover, this study concluded that the use of probiotics or synbiotics did not significantly impact weight gain. Conclusion: Probiotics demonstrated efficacy in reducing the duration of diarrhea, but not its incidence, potentially contributing to improved recovery outcomes. However, their impact on weight gain in children with SAM remains inconclusive. Further research with larger studies is warranted to identify factors influencing probiotic efficacy and to explore their potential role in the comprehensive management of SAM.